A SOCIOLOGICAL APPROACH OF THE WOMAN’S POSITION AND RIGHT IN JAMES CAMEROON’S MOVIE OF TITANIC. - Netty Herawati (Universitas Riau Kepulauan, 2012)
This study is about a sociological approach of woman position and right based on the Titanic Movie of the great- art durector, James Cameroon. This study describes how woman has lower position in society and her right was neglected as well. This study explains that Rose (female-main character) could break the barrier of her society, and she could get her right in choosing her future husband.